THE IMPACT OF SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE WITH AUDIT QUALITY AS A MODERATION VARIABLE IN INDONESIA - Meviani, Regita Shinta Arta; Syafruddin, Muchamad (DIPONEGORO UNIVERSITY, 2023)
This research aims to examine the impact of social responsibility on financial performance with audit quality as a moderating variable in Indonesia. This study uses data from 31 Indonesian companies registered during the 2016–2021 period. Direct and moderating effects were tested using multiple regression techniques. Researchers found that CSR had a positive effect on company financial performance as proxied by return on equity (ROE) and a negative effect on company financial performance as proxied by return on assets (ROA) and Tobin's Q (TQ). One of the limitations of this research is the selection of independent variables. The author is limited to one variable, namely CSR involvement.Further studies could consider other independent variables, such as company age, industry type, board composition, etc., to provide an in-depth analysis of the drivers of a company's financial performance. These findings have practical implications that may be useful for managers in corporate management. The manager encourages all board members to seriously consider investing in developing strategies that promote social behavioral components to improve overall company performance. This research adds to the current literature on CSR by revealing the impact of external auditor quality on the relationship between CSR and financial performance. In addition, the author examines each CSR indicator, namely environmental, social and governance.